Absorption of Metal Ions and Dyes in Liquid Waste : A Literature Review - Indah, Dahlia Rosma; Afriani, Aulia; Nurwahidah, Nurwahidah (Universitas Pendidikan Mandalika, 2024)
Industrial development and population growth cause a lot of waste to enter water bodies, causing pollution. A number of studies have been carried out to remove metal ions and dyes in waters. Adsorption is the most widely used method to absorb heavy metal ions and harmful dyes by utilizing natural resources that are still abundant, for example, agricultural, livestock, and fishery waste. Adsorption can also use activated or modified absorbent materials to increase porosity and expand the surface plane. In this review, the adsorption method and results obtained by the researcher with various absorbent materials are summarized which are mostly carried out in the last ten years. The purpose of this review is to provide input in finding alternatives to other absorbent materials or eliminating pollutants harmful to human health and the environment.